2015
DOI: 10.1038/ijo.2015.174
|View full text |Cite
|
Sign up to set email alerts
|

Changes in inflammation, oxidative stress and adipokines following bariatric surgery among adolescents with severe obesity

Abstract: Background/Objectives Inflammation, oxidative stress, and dysregulation of adipokines are thought to be pathophysiological mechanisms linking obesity to the development of insulin resistance and atherosclerosis. In adults, bariatric surgery reduces inflammation and oxidative stress, and beneficially changes levels of several adipokines, but little is known about post-surgical changes among adolescents. Subjects/Methods In two separate longitudinal cohorts we evaluated change from baseline of interleukin-6 (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
60
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 41 publications
14
60
1
Order By: Relevance
“…TNF-α concentrations are not modified by bariatric surgery. 37 This is in contrast with findings with regard to high-sensitivity C-reactive protein, interleukin-6, and plasminogen activator inhibitor-1 levels, which increased during TODAY follow-up. 4 By the end of the study, TNF-α concentrations showed an association with LV mass, BP, and HbA1c.…”
Section: Discussionmentioning
confidence: 67%
“…TNF-α concentrations are not modified by bariatric surgery. 37 This is in contrast with findings with regard to high-sensitivity C-reactive protein, interleukin-6, and plasminogen activator inhibitor-1 levels, which increased during TODAY follow-up. 4 By the end of the study, TNF-α concentrations showed an association with LV mass, BP, and HbA1c.…”
Section: Discussionmentioning
confidence: 67%
“…Even prior to significant weight loss, the surgical treatment reverses metabolic syndrome-related diseases, such as type 2 diabetes, hypertension, dyslipidemias, polycystic ovary syndrome, and non-alcoholic steatosis hepatitis [17]. While insulin levels return back to normal rates within days after bariatric surgery, it takes many months to recover insulin resistance as well as inflammation and oxidative stress in adipose tissue [18,19,20]. Five studies have focused on the effect of bariatric surgery on oxidative stress [40,41,42,48,50].…”
Section: Resultsmentioning
confidence: 99%
“…The treatment reverses obesity-associated diseases such as type 2 diabetes, hypertension, dyslipidemias, and polycystic ovary syndrome [17]. Bariatric surgery has been shown to affect biological mechanisms like inflammation and oxidative stress in adipose tissue [18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…In the same study, insulin resistance was also found to be reduced, which could have an important role in the amelioration of T2DM and, thus, in the reduction of long-term mortality. A study in adolescents undergoing RYGBP and SG also showed that the levels of IL-6, TNF-α, MCP-1, oxidized low-density lipoprotein cholesterol, and leptin significantly decreased while adiponectin increased, indicating a marked decrease in systemic inflammation and oxidative stress [22]. Consistently with the previously cited studies on RYGBP, Brethauer et al [23] demonstrated a decrease in inflammatory cytokines and also a decrease in the levels of C-reactive protein, fasting insulin, and fibrinogen, along with an amelioration in arterial endothelial function, a further surrogate marker of cardiovascular risk reduction after RYGBP.…”
Section: Bs and Inflammationmentioning
confidence: 99%
“…On the contrary, systemic and adipose-tissue inflammation seems to decrease following bariatric procedures both at the biochemical and at the clinical level. These changes supposedly promote risk reduction in obesity-associated comorbid conditions including T2DM, cardiovascular diseases, infections, and cancer [20,21,22,23]. …”
Section: Bs and Inflammationmentioning
confidence: 99%